2001
DOI: 10.1289/ehp.01109229
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of sexual development in male rats with in utero and lactational exposure to the antiandrogenic plasticizer Di(2-ethylhexyl) phthalate.

Abstract: Several members of the phthalate ester family have antiandrogenic properties, yet little is known about how exposure to these ubiquitous environmental contaminants early in development may affect sexual development. We conducted experiments to determine effects of in utero and lactational exposure to the most prevalent phthalate ester, di(2-ethylhexyl) phthalate (DEHP), on male reproductive system development and sexual behavior. Sprague-Dawley rats were dosed with corn oil or DEHP (0, 375, 750, or 1,500 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(116 citation statements)
references
References 49 publications
(62 reference statements)
5
108
1
2
Order By: Relevance
“…Their teratogenicity is also well established as reproductive toxicants [35,36]. Our results show the biological effects of unconjugated DEHP on the induction of autoimmunity.…”
Section: Discussionsupporting
confidence: 54%
“…Their teratogenicity is also well established as reproductive toxicants [35,36]. Our results show the biological effects of unconjugated DEHP on the induction of autoimmunity.…”
Section: Discussionsupporting
confidence: 54%
“…In recent years, however, phthalate esters have been implicated in a number of adverse health effects such as cancer (IARC 2000;Dearman et al 1996) and damage to the reproductive system as endocrine disruptors (Yang et al 2009;Swan 2008;Silva et al 2005;Kato et al 2005;Duty et al 2005;Moore et al 2001;Call et al 2001;Blount et al 2000;Ema et al 2000;Harris et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several PAEs are carcinogenic in animal models (Huber et al, 1996). In addition, some PAEs and their metabolic products act functionally as antiandrogens during the prenatal period (Mylchreest et al, 1998;Moore et al, 2001) and cause reproductive and developmental toxicities in animals (Agarwal et al, 1986). Recent investigations have shown that several PAEs are environmental hormones (Kambia et al, 2001).…”
Section: Introductionmentioning
confidence: 99%